Associations Between Characteristics of Obstructive Sleep Apnea and Nocturnal Blood Pressure Surge. Issue 5 (November 2018) - Sasaki, Nobuo; Nagai, Michiaki; Mizuno, Hiroyuki; Kuwabara, Mitsuo; Hoshide, Satoshi; Kario, Kazuomi
Abstract : Research suggests that oxygen desaturation and sleep stage during obstructive sleep apnea (OSA) are related to the magnitude of high blood pressure (BP) in a laboratory setting. However, in a clinical setting, these associations have not been well studied. We used a noninvasive oscillometric BP measurement device to investigate the association between oxygen-triggered BP levels at the end of each OSA episode and the characteristics of the preceding OSA episode. In 42 newly diagnosed OSA patients (average age, 63.5±12.5 years; average apnea-hypopnea index, 32.6±18.2 per hour), 258 BP measurements were obtained at the end of OSA episodes. Hypoxia-peak systolic BP (SBP), defined as the maximum oxygen-triggered SBP value, was significantly higher in rapid eye movement sleep (144.9±19.9 mm Hg) than in non–rapid eye movement stage 1 sleep (129.5±15.1 mm Hg; P <0.001) and non–rapid eye movement stage 2 sleep (129.4±14.7 mm Hg; P <0.001). In a multivariate-linear mixed model, the lowest oxygen saturation percentage during each OSA episode was associated with increased hypoxia-peak SBP (−0.501 mm Hg; P <0.001), nocturnal SBP surge (−0.395 mm Hg; P <0.001), defined as the difference between the hypoxia-peak SBP and the mean nocturnal SBP, and maximum value of SBP surge (−0.468 mm Hg; P <0.001), defined as the difference between the hypoxia-peak SBP and the minimum nocturnal SBP independent of sleep stage. These values were not associated with the duration of each OSA episode. The contribution of rapid eye movement sleep and severe oxygen desaturation to OSA-related BP elevation measured with a noninvasive oscillometric method was determined in a clinical setting. Abstract : Supplemental Digital Content is available in the text.